Investigating the use of partial napping with ultra-flash profiling to identify flavour differences in replicated, experimental wines. (2nd October 2018) - Kemp, Belinda; Pickering, Gary; Willwerth, James; Inglis, Debra
ABSTRACT: Experimental wine studies with three or more treatments, over multiple years with replicated wines, often require sensory analysis to describe treatment effects on the resultant wines. This scientific approach can result in a large number of samples for sensory analysis, which can be time-consuming, and problematic for the design of descriptive analysis (DA). The aim of this study was to establish whether partial napping (PN) combined with ultra-flash profiling (UFP) could identify a subset of replicate wines that were similar enough in flavour profile that they could be used as representative samples for descriptive analysis (DA). Pinot noir wines from three field treatments (T1, T2, and T3), were produced in triplicate (a, b and c) and analysed by PN and UFP. Multiple factor analysis (MFA) using a citation frequency method showed that two similar replicate wines could be identified for each treatment wine. These results show that UFP allows for small sample sets to be used for subsequent and more resource intensive DA methods, and provides greater insight into the use of rapid sensory analysis in wine research.